2022
DOI: 10.3389/fbioe.2022.934997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of unsulfated biotechnological chondroitin in a knee osteoarthritis mouse model as a potential novel functional ingredient in nutraceuticals and pharmaceuticals

Abstract: Osteoarthritis is a very disabling disease that can be treated with both non-pharmacological and pharmacological approaches. In the last years, pharmaceutical-grade chondroitin sulfate (CS) and glucosamine emerged as symptomatic slow-acting molecules, effective in pain reduction and improved function in patients affected by osteoarthritis. CS is a sulfated glycosaminoglycan that is currently produced mainly by extraction from animal tissues, and it is commercialized as a pharmaceutical-grade ingredient and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In recent times, scientific investigations have suggested that CS, alone or in combination with other GAGs, may enhance chondrocyte metabolism, counteract the inflammatory process, and down-regulate the degradative enzymes [20,37]. In this context, the biological properties of BC have lately been tested in an OA animal model [43]. Thus, Cimini et al [43] displayed that BC was as effective in reducing pain and affecting different specific biomarkers related to the inflammatory/degradation progression as CS in an OA mice model, highlighting the possibility of being able to replace extractive chondroitin with the biotechnological one.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, scientific investigations have suggested that CS, alone or in combination with other GAGs, may enhance chondrocyte metabolism, counteract the inflammatory process, and down-regulate the degradative enzymes [20,37]. In this context, the biological properties of BC have lately been tested in an OA animal model [43]. Thus, Cimini et al [43] displayed that BC was as effective in reducing pain and affecting different specific biomarkers related to the inflammatory/degradation progression as CS in an OA mice model, highlighting the possibility of being able to replace extractive chondroitin with the biotechnological one.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring additional methods to treat chondrocyte-related diseases is crucial due to the significant medical challenge posed by abnormal chondrogenesis and the defects observed in conditions like osteoarthritis, which currently have limited treatment options. Recent studies have explored the potential of biotechnological chondroitin (BC) as an alternative to traditional chondroitin sulfate (CS) for treating osteoarthritis [ 44 ]. The results indicate that BC, akin to CS, effectively reduces mechanical allodynia, decreases cartilage damage, and attenuates inflammation- and pain-related biochemical markers in an osteoarthritic mouse model induced by MIA (Monosodium Iodoacetate).…”
Section: Discussionmentioning
confidence: 99%
“…Each day, formula was made based on daily weights and the caloric needs of the pups from the batch stock and supplemented with 0.008 mg/g of Lipopolysaccharide (LPS) isolated from Escherichia Coli O111:B4 (cat # L4391, Sigma‐Aldrich Company, St. Louis, MO). Those in the group to receive chondroitin sulfate, had their formula supplemented to receive 0.2 mg/g chondroitin sulfate daily (Cimini et al, 2022 ; Gao et al, 2022 ; Qi et al, 2021 ; Singh et al, 2021 ; Song et al, 2017 ). Experimental pups were gavage fed a hyper‐concentrated formula (300 kcal/kg/day) three times per day using a 1.9 French catheter.…”
Section: Methodsmentioning
confidence: 99%
“…A certificate of analysis was provided by the company for the lot number used in these experiments. The dose of chondroitin sulfate was determined by a literature search of chondroitin sulfate doses in different rodent models of disease that all used a dose of 200 mg/kg for beneficial therapeutic effects (Cimini et al, 2022 ; Gao et al, 2022 ; Qi et al, 2021 ; Singh et al, 2021 ; Song et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%